Mobility models and traffic pattern generation-based optimisation of reactive protocols. (1st January 2013) - Karia, Deepak C.; Godbole, V.
Mobile ad-hoc network is a collection of wireless mobile hosts forming a temporary network without the aid of any stand-alone infrastructure or centralised administration. Mobile ad-hoc networks are self-organising and self-configuring multi-hop wireless networks where the structure of the network changes dynamically. This is mainly due to the mobility of the nodes. The primary objective of this paper is to investigate the performance measures of AODV, AOMDV and DSR routing protocols by using nomadic community mobility model, random direction mobility model and pursue mobility model. The metrics used for performance analysis are routing overhead, normalised routing load, average end-to-end delay, throughput, routing cost and packet delivery ratio.